Three new terpenoids from the Eupatorium chinense. (June 2017) - Yu, Xiao-Qin; Zhang, Qing-Qing; Yan, Wei-Hong; Wang, Lei; Guo, Zhi-Yong; Yang, Qing-Qing; Liu, Cheng-Xiong; He, Hai-Bo; Zou, Kun
Graphical abstract: Highlights: Three new terpenoids compounds were isolated from the whole plant of Eupatorium chinense. . The structures of the isolated compounds were elucidated by spectroscopic means. All of the isolated compounds were tested in vitro for their cytotoxic activities against four cancer cell lines. Abstract: Three new terpenoids compounds (1–3 ) were obtained from ethyl acetate fraction, which was yielded from Eupatorium chinense ' s ethanol extract . Their structures were determined on the basis of 1D and 2D NMR spectroscopy, including 1 H- 1 H COSY, HMBC, HSQC and NOESY experiments. All of the isolated compounds were tested in vitro for their cytotoxic activities against the HepG2, HGC-27 and MDA-MB-231 cancer cell lines.